2014
DOI: 10.1537/ase.140615
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between jugular foramen asymmetry and superior sagittal venous sinus laterality

Abstract: The reason for asymmetry of the jugular foramen (JF) size is unclear, with previous suggestions including that handedness may influence development of a larger JF on the ipsilateral side of handedness. Intracranial venous asymmetry has not previously been considered in relation to JF size. We aim to investigate if the asymmetry of the superior sagittal venous sinus (SSVS) drainage is related to JF size. Two hundred and forty-five skulls from collections in Otago, New Zealand (Indian skulls) and Coimbra, Portgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Left-right asymmetry in orbital height or breadth was previously reported in Egyptian [2] and Nigerian [20] populations; morphological asymmetry is not unique to this region and was identified in other morpho- logical features such as the jugular foramen and the superior sagittal sinus. [31] However, the majority of studies published on OI indicate left-right symmetry, though some of these observed differences were not statistically significant. Left-right orbital index asymmetry is poten-tially a novel finding and may be a characteristic unique to our population of skulls.…”
Section: Orbital Indexmentioning
confidence: 93%
“…Left-right asymmetry in orbital height or breadth was previously reported in Egyptian [2] and Nigerian [20] populations; morphological asymmetry is not unique to this region and was identified in other morpho- logical features such as the jugular foramen and the superior sagittal sinus. [31] However, the majority of studies published on OI indicate left-right symmetry, though some of these observed differences were not statistically significant. Left-right orbital index asymmetry is poten-tially a novel finding and may be a characteristic unique to our population of skulls.…”
Section: Orbital Indexmentioning
confidence: 93%
“…It is located at the skull base, lateral to the foramen magnum, posterior and medial to the base of the styloid process of the temporal bone, slightly lateral and posterior to the carotid canal and lateral to the hypoglossal nerve canal. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%
“…The internal jugular vein, the main venous drainage pathway of the brain, and three cranial nerves, the glossopharyngeal nerve or cranial nerve IX, the vagal nerve or cranial nerve X and the accessory or cranial nerve XI, pass through the jugular foramen, also called the posterior lace rum, 3 to reach the neck. The inferior petrosal sinus, which drains blood from the cavernous sinus to the jugular bulb or to the internal jugular vein itself, and one or more branches of the ascending pharyngeal artery or the occipital artery to the meninges, 1 , 2 , 4 are also found in the jugular foramen region.…”
Section: Introductionmentioning
confidence: 99%